Efektivitas Penggunaan Pewarna Metilen Blue dalam Pengamatan Bentuk Sel pada Kulit Katak - Azzahra Nabilla Atha; Erika Dwi Susanti; Azizah Zahra Nur Fitria; Erlanda Islami Pasha; Elsa Trisna Sari; Nur Aini Fatna Fadilla; David Valentino Iskandar; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to evaluate the effectiveness of using Methylene Blue stain in the microscopic observation of frog skin cell structures. Cell staining is an essential technique in histological studies, as it enhances the visibility of cellular components that are otherwise difficult to observe without contrast. Methylene Blue is known to have a high affinity for acidic components within the cell nucleus, thus providing a clearer depiction of nuclear and cell membrane structures. This research employed a descriptive experimental method by preparing frog skin tissue samples stained with Methylene Blue and observing them under a light microscope. The results indicated that Methylene Blue staining produced high contrast, allowing for the identification of hexagonal-shaped cells and dark, centralized nuclei. The obtained microscopic images revealed a uniform distribution of cells with clearly observable morphological structures. Therefore, Methylene Blue is proven to be effective in enhancing the microscopic visualization of epithelial tissue in frog skin and is recommended for use in both educational and basic biological research contexts.